A survey of the knowledge, attitude, and awareness about the principal choice of intracanal medicaments among the general dental practitioners and nonendodontic specialists - Madhu Priya Manohar; Subash Sharma (Wolters Kluwer Medknow Publications, 2018)
Background: Removal of the microbial organisms from the root canal system is a prerequisite for the successful outcome of any root canal treatment. Use of an effective intracanal medicament will assist in the disinfection of the root canal system. Intracanal medicaments have been used to disinfect root canals between appointments and reduce interappointment pain. Materials and Methods: A questionnaire survey was conducted to evaluate the knowledge, attitude, and awareness about the principal choice of intracanal medicaments among general dental practitioners and nonendodontic specialists. The questionnaire consisted of 11 questions related to intracanal medicaments in Endodontics. It was distributed to 75 general dental practitioners and 75 other specialists (nonendodontists). Results: In the present study, the authors observed that the knowledge level among the study participants was moderately satisfying. However, the need for more education of the dentists with regard to the intracanal medicaments was perceived. Discussion: Correct knowledge of intracanal medicaments would help the practitioners to decide the apt material of choice as intracanal medicaments in different clinical situations. Conclusion: The present study highlighted the need for more continuing dental education programs with active participation of general practitioners and nonendodontic specialists to update themselves.